Herbicidal Formulations with Plant-Based Compounds to Control Amaranthus hybridus, Lolium multiflorum, and Brassica rapa Weeds - Romero, Juan J. (2025)
Numerous studies have shown the potential effect of bioactive agents against weeds. In this study, we developed two binary formulations with nonanoic acid, citral, or thymoquinone as herbicides and evaluated their physicochemical properties. The presence of the bioactive compounds in the formulations was confirmed through FTIR spectroscopy. A dynamic light scattering study was conducted to characterize the emulsified formulations and the size and distribution of the aggregates. In addition, thermogravimetric analysis was performed to ensure the thermal stability of the formulations. The herbicidal activity against Amaranthus hybridus, Lolium multiflorum, and Brassica rapa weeds was evaluated, and each species showed different levels of sensitivity with half maximal inhibitory concentration doses from 0.07 to 5 mM. The binary formulations negatively affected the photosynthetic system reducing Fv/Fm values at 5 days after treatment. Lastly, the phytotoxic effect of the formulations was tested on wheat germination, and they did not inhibit plant germination and seedling growth at ≤5 mM after 14 days of application. The development of new formulations with natural compounds as bioactive ingredients would allow control of a wide spectrum of weeds through a multitarget-site effect.